Review of nanostructured devices for thermoelectric applications - Pennelli, Giovanni (Beilstein Journal of Nanotechnology, 2014)
A big research effort is currently dedicated to the development of thermoelectric devices capable of a direct thermal-to-electrical energy conversion, aiming at efficiencies as high as possible. These devices are very attractive for many applications in the fields of energy recovery and green energy harvesting. In this paper, after a quick summary of the fundamental principles of thermoelectricity, the main characteristics of materials needed for high efficiency thermoelectric conversion will be discussed, and a quick review of the most promising materials currently under development will be given. This review paper will put a particular emphasis on nanostructured silicon, which represents a valid compromise between good thermoelectric properties on one side and material availability, sustainability, technological feasibility on the other side. The most important bottom-up and top-down nanofabrication techniques for large area silicon nanowire arrays, to be used for high efficiency thermoelectric devices, will be presented and discussed.
Keywords: nanofabrication; nanostructures; silicon nanowires; thermoelectricity